Development of PVA-Carrageenan based Scaffolds and Evaluating Its Efficacy on Osteosarcoma Upon Cryopreservation - Chopra, Pankaj (My University, 2015)
The present study investigates and shows the fabrication of porous 3D, biodegradable scaffolds using PVA & Carrageenan by crosslinking in different ratios(5:5, 6:4, 7:3, 8:2, 9:1). They are characterized by SEM, ATR-FTIR. The biocompatibility study was done by hemolysis. They were seeded with cells and cryopreserved for 15 days where each sample is taken out every 3rd day and cell viability was evaluated.
Master of Science (Biotechnology)
Keywords: Scaffold; PVA; Carrageenan; Cell Attachment; Cryopreservation; Saos-2; DBT